Experimental determination of single molecule toroic behaviour in a Dy8 single molecule magnet. Issue 32 (2nd August 2019) - Zhang, Qing; Baker, Michael L.; Li, Shiqi; Sarachik, Myriam P.; Baldoví, José J.; Gaita-Ariño, Alejandro; Coronado, Eugenio; Alexandropoulos, Dimitris I.; Stamatatos, Theocharis C.
Abstract : Multi-orientation single-crystal magnetisation measurements unpick the spin structure of Dy8, identifying a canted antiferrotoroidic tetramer ground-state with slow magnetic relaxation. Abstract : The enhancement of toroic motifs through coupling toroidal moments within molecular nanomagnets is a new, interesting and relevant approach for both fundamental research and potential quantum computation applications. We investigate a Dy8 molecular cluster and discover it has a antiferrotoroic ground state with slow magnetic relaxation. The experimental characterization of the magnetic anisotropy axes of each magnetic center and their exchange interactions represents a considerable challenge due to the non-magnetic nature of the toroidal motif. To overcome this and obtain access to the low energy states of Dy8 we establish a multi-orientation single-crystal micro Hall sensor magnetometry approach. Using an effective Hamiltonian model we then unpick the microscopic spin structure of Dy8, leading to a canted antiferrotoroidic tetramer molecular ground state. These findings are supported with electrostatic calculations that independently confirm the experimentally determined magnetic anisotropy axes for each Dy III ion within the molecule.